Perceptions of the urban walking environments - Raja Ariffin, Raja Noriza; Zahari, Rustam Khairi (Elsevier, 2013)
Walkability is the basis of sustainable city. Walking is the socially equitable mode that is most accessible to the masses. However, the advent of transportation technology, such as automobile and superhighway has degraded the pedestrian environment. The aim of the paper is to examine the characteristics or attributes that could promote walking activities via people's perceptions. This paper combines survey questionnaire and walkability audit to gauge perception of the urban walking environment. Findings indicate that the proximity of destinations, good weather condition, safety and well-designed pedestrian facilities can significantly contribute to better perceptions of the walking environment.